Determinants of technology-based spin-offs created by universities in Korea. Issue 2 (3rd May 2020) - Kim, HanJun
ABSTRACT: This study provides an empirical analysis on how the endogenous and exogenous factors of universities influence the creation of technology-based spin-offs (TBSOs), employing unique datasets from the Korean government-affiliated research institute. The results support the conclusion that universities with experienced technology licensing offices (TLOs), those in possession of incubation policies or business incubators, and those willing to participate in external collaboration with parties in and outside Korea have an edge in creating TBSOs. This study also reveals that the moderating effect between universities' external collaboration and the personnel sizes at their technology licensing offices negatively affect the creation of TBSOs. The findings of this study shed some lights on policymakers as well as scholars.